Anatomy, Posture, Prevalence, Pain, Treatment and Interventions of Musculoskeletal Disorders - Korhan, Orhan (IntechOpen, 2018)
Musculoskeletal disorders are defined as disorders that affect a part of the body's musculoskeletal system, which includes bones, nerves, tendons, ligaments, joints, cartilage, blood vessels, and spinal disks. These are the injuries that result from repeated motions, vibrations, and forces placed on human bodies while performing various job actions. They are extremely common and costly problems for people and companies. Thus, this book is designed to include a wide array of extensive and comprehensive discussions provided on occupational, educational, and medical aspects of ergonomics. Thus, it can be utilized as a guide to identify and analyze the risk factors, reveal the impact of prevention and intervention, and discuss treatment of musculoskeletal disorders.